Stronger selective constraints on the mitochondrial genome in flying fishes - Ding, Zufa; Xu, Youwei; Chen, Wenjun; Liu, Yang; Wang, Cheng; Niu, Yuhan; Zhang, Kui; Wang, Ying; Yang, Liandong (Frontiers in Marine Science, 2023)
Flying fishes, which use their wing-like pectoral fins and hypocercal caudal fin to glide through the air to avoid underwater predators, have independently evolved flight behavior, making them ideal for the study of adaptive evolution. To investigate the adaptation of flight behavior in flying fishes and the origin of Beloniformes fishes, this study obtained the complete mitochondrial genomes of Cheilopogon nigricans and Oxyporhamphus micropterus and constructed the DNA sequences extracted from these newly sequenced mitochondrial genomes with the DNA sequences of 32 previously published mitochondrial genomes into a dataset for reconstructing the phylogenetic relationships of Beloniformes fishes. The phylogeny that emerged strongly supported the possibility that flying fishes developed from halfbeaks and the progressive transition of flying fishes from two-wing to four-wing gliding. The divergence time analysis showed that the split between the suborder Belonidei and the family Adrianichthyidae occurred roughly 77.08 Mya, which fell within the period of evolution of the Indian plate in the late Cretaceous. Selection analyses revealed that flying fishes have a lower dN/dS ratio than the other members of Beloniformes, indicating that flying fishes experienced stronger purifying selection to eliminate deleterious mutations to maintain efficient energy metabolism to adapt to flight behavior. Moreover, this work found the positively selected signal in the ND4 gene, suggesting that different mitogenomic genes might have undergone different selective patterns during adaptive evolution.